2012 Olympic Games - terrorist CBRE threat estimate and medical response. (27th June 2012) - Galatas, Ioannis
2012 is the year of the Olympic Games that will be held in London, UK. This mega sport event is a terrorist challenge especially now that Osama bin Laden is dead and his successor is struggling to regain 'face' amongst Islamic extremists opposing West. New emerging threats such as CBRE agents' release in urban/megapolis environment must be taken seriously and state response must be fortified against this visible possibility. Medical/hospital CBRE defence and preparedness is of mandatory importance because medical consequences might last for months or years. A terrorist CBRE threat estimate is provided and an analysis of hospital preparedness is provided in order to assist first responders perform in a most effective way in order to minimise casualties and consequences. Following Japan's triple catastrophe nobody has the right to consider CBRN release as science fiction. It might happen to us as well! Tomorrow!